2002
DOI: 10.1007/bf02982046
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Acceleration of Disease Progression Following Cyclosporin A Treatment in a Patient With Myelodysplastic Syndrome

Abstract: A 38-year-old Japanese man with myelodysplastic syndrome (MDS), whose bone marrow smears demonstrated hypercellularity, was treated with oral cyclosporin A (CsA) therapy. During the course of this therapy, the numbers of peripheral blood and bone marrow blasts increased and the level of serum lactate dehydrogenase increased. After discontinuation of CsA treatment, all of these levels rapidly decreased. We consider that CsA might accelerate disease progression in certain MDS cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Therefore, such genetic instabilities may be resolved simply by discontinuation of cytotoxic (i.e., immunosuppressive) drugs or patient's innate immunity in some specific conditions. A reported case of primary MDS which was improved simply by discontinuation of cyclosporine A may also support this hypothesis [10]. While high-dose CY or IFM previously administered cannot be ruled out, the probable source drug for t-MDS in our patient is CY administered in low doses chronically until just prior to onset, since discontinuation of CY resulted in remission of t-MDS.…”
Section: Discussionsupporting
confidence: 51%
“…Therefore, such genetic instabilities may be resolved simply by discontinuation of cytotoxic (i.e., immunosuppressive) drugs or patient's innate immunity in some specific conditions. A reported case of primary MDS which was improved simply by discontinuation of cyclosporine A may also support this hypothesis [10]. While high-dose CY or IFM previously administered cannot be ruled out, the probable source drug for t-MDS in our patient is CY administered in low doses chronically until just prior to onset, since discontinuation of CY resulted in remission of t-MDS.…”
Section: Discussionsupporting
confidence: 51%
“…Concerns have been raised about cyclosporine accelerating disease progression in some MDS patients. 15 Our case may be further evidence to this muchquestioned tumor-promoting potential of cyclosporine. 16,17 Use of cyclosporine resulting in the development of a new karyotypic abnormality, leading to progression of RA to refractory anemia with excess blasts has also been previously reported.…”
Section: Discussionmentioning
confidence: 78%
“…Clinical trials of Immunosuppression therapy (IST) also showed that hematological response could only be achieved in part of MDS patients (response rate 30-60%). On the contrary, IST was considered to have accelerated disease evolvement in some cases (Itoh et al, 2002). So it is important to decide which group of patients may benefit from IST before the treatment start.…”
Section: Discussionmentioning
confidence: 99%